Development of new polymer composite materials for the flooring of rail carriage - Olmos Irikovich, Zaynitdinova; Rustam Vyacheslavovich, Rahimov; Mahmod Lafta, Waail; Yadgor Ozodovich, Ruzmetov (International Journal of Engineering and Technology, 2020)
The subject of improving the competitiveness and efficiency of railway rolling stock is highly demanded as the railway transport consider the nerve of the goods transport in the hole word. One of the requirements to develop the railway transport related to the continuous improvement of existing materials and find a new material which would satisfy such conflicting requirements as relia-bility, sustainability, producibility and the manufacturing process automation possibility. The researches show that use of polymer composite materials (PCM) in the production of both passenger and freight railway rolling stock, provides lightweight, improves its performance, increases durability and reduces operating costs.Â